Dry reforming of methane in DBD plasma over Ni-based catalysts: influence of process conditions and support on performance and durability - Ray, Debjyoti; Nepak, Devadutta; Janampelli, Sagar; Goshal, Partha; Subrahmanyam, Ch (Energy Technology, 2019)
The conversion of greenhouse gases, H-2 and CO selectivity, H-2/CO ratio, and carbon formation in the dry reforming reaction over Ni-supported ZSM-5, Al2O3, and TiO2 are tested under thermal, plasma, and plasma-thermal conditions. It is observed that the dielectric nature, specific surface area, and acid-base properties of the support influence the performance during the DRM reaction. Typical results indicate that the best activity and syngas yield are achieved with 15Ni/Al2O3 under plasma conditions, possibly due to the high dielectric constant and surface area of Al2O3 and nanosize of Ni. In the thermal condition, the highest conversion of 73% and 68% for CH4 and CO2, respectively, is achieved over 15Ni/ZSM-5 at 500 degrees C. Plasma-assisted thermal conditions provide the highest conversion due to the activation of reactants and their partial conversion in the plasma zone before entering into the catalytic zone. The plasma-assisted thermocatalytic conversions of CH4 and CO2 reach the best values of 76% and 71%, respectively, on 15Ni/ZSM-5. Under the same conditions, 68% and 65% conversion of CH4 and CO2, respectively, is achieved with 15Ni/Al2O3 where the selectivity for H-2 and CO is 45% and 58%, respectively.
Keywords: DBD plasma; Dry reforming; reaction conditions; supported catalysts; Syngas